Deposit Insurance : Actual and Good Practices - Garcia, G. (Occasional Papers; Occasional Paper ;, 2000)
This paper demonstrates a well-designed deposit guarantee system can strengthen incentives for owners, managers, depositors and other creditors, borrowers, regulators and supervisors, and politicians. Borrowers should be aware that they will have to repay their loans if their bank fails and will be encouraged to keep their loans current where offsetting is limited to past-due loans. The performance of insurers, regulators, and supervisors as agents will improve where they know that they can take justifiable actions without political interference and will be held accountable for their actions to their principals. Despite the improvements, and possibly partly because there are issues in deposit insurance design that remain to be resolved, financial crises have been prevalent during the 1990s. This situation has forced a number of countries to offer a blanket guarantee to restore confidence and to allow the continued functioning of the financial system while the authorities take time to design a plan for the resolution of the crisis.